The Influence of Customer Satisfaction, Application Quality and Price Perception on Customer Loyalty in the GRAB Application - Ega Amalia; Anggara Dimar; Susi Oktavia (Yayasan Gema Bina Nusantara, 2023)
This research aims to determine the influence of customer satisfaction, price quality, and price perception on customer loyalty. Researchers used descriptive methods and a post-positivistic paradigm. The sample used was 73 students who had made transactions on the GRAB application. The data collection technique uses a questionnaire. The data analysis used in this research uses quantitative analysis. In-depth data analysis techniques for quantitative research using regression. Researchers use parametric statistics based on the nature of the data analyzed on an interval scale. Based on the discussion of the research results that have been conducted, it can be concluded that customer satisfaction, application quality, and price perceptions have no influence on customer loyalty. In the data obtained, the majority of respondents were satisfied with the service. The data results show that the service they feel is quite good but still not optimal. If the application can improve service in accordance with customer expectations, a positive perception of the application will arise, and customer loyalty towards the application will increase. According to the results of the data analysis, the majority of respondents felt that the quality of the application was very good. This has a positive effect because it can fulfill customer satisfaction through the application. For price perceptions, the data shows that pricing is good enough but not optimal. For this, you can adjust rates according to customer perceptions.